2016
DOI: 10.1002/for.2425
|View full text |Cite
|
Sign up to set email alerts
|

Severity Prediction of Traffic Accident Using an Artificial Neural Network

Abstract: In this paper, an artificial neural network (ANN) was used to predict the injury severity of traffic accidents based on 5973 traffic accident records occurred in Abu Dhabi over a 6‐year period (from 2008 to 2013). For each accident record, 48 different attributes had been collected at the time of the accident. After data preprocessing, the data were reduced to 16 attributes and four injury severity classes. In this study, WEKA (Waikato Environment for Knowledge Analysis) data‐mining software was used to build … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(74 citation statements)
references
References 11 publications
0
61
0
Order By: Relevance
“…In these studies, the ANN prediction accuracy ranged between 55% and 65%. On the other hand, the ANN model by [46] resulted in overall prediction accuracy for the testing data of 74.6%. However, although their model could predict moderate and minor injuries with 81.6% and 74.6%, respectively, the model could not predict fatal and severe injuries at all.…”
Section: Artificial Neural Networkmentioning
confidence: 98%
“…In these studies, the ANN prediction accuracy ranged between 55% and 65%. On the other hand, the ANN model by [46] resulted in overall prediction accuracy for the testing data of 74.6%. However, although their model could predict moderate and minor injuries with 81.6% and 74.6%, respectively, the model could not predict fatal and severe injuries at all.…”
Section: Artificial Neural Networkmentioning
confidence: 98%
“…It was found that MLP was superior when compared with ART and OL. Alkheder et al [ 12 ] developed a NN model for the severity prediction of RTC in Abu Dhabi, UAE. A k-means clustering algorithm was used to cluster the crash dataset into three clusters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ANNs can be used in various powerful ways: to teach non-linear system dynamics without any mathematical modeling [38][39][40], to analyze and generalize from samples and to make predictions, to memorize the features of given data, and to match or make associations from new data to old data [41]. In transportation research, many studies have applied ANN models to predict traffic accidents and severity [42][43][44], and such models have shown greater accuracy in predicting injury severity compared to other traditional methods, including ordered probit modeling [45]. On the other hand, ANN is disadvantageous for interpreting human factors to predict traffic accident severity [26].…”
Section: Artificial Neural Networkmentioning
confidence: 99%